Power games in war and peace : the tragic impact of corruption, violence, and impunity on the Sri Lankan child - De Silva, Harendra (Colombo : Harendra de Silva, 2003)
On the social conditions of Sri Lankan children as an aftermath of the political instability post 1994.
Keywords: Children -- Sri Lanka -- Social conditions; Children and war -- Sri Lanka; Sri Lanka -- Politics and government -- 1978-